2017
DOI: 10.1021/acsomega.7b00954
|View full text |Cite
|
Sign up to set email alerts
|

Hsp72 Is an Intracellular Target of the α,β-Unsaturated Sesquiterpene Lactone, Parthenolide

Abstract: The electrophilic natural product parthenolide has generated significant interest as a model for potential chemotherapeutics. Similar to other α,β-unsaturated carbonyl electrophiles, parthenolide induces the heat shock response in leukemia cells, potentially through covalent adduction of heat shock proteins. Other thiol-reactive electrophiles have also been shown to induce the heat shock response as well as to covalently adduct members of the heat shock protein family, such as heat shock protein 72 (Hsp72). To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…S1). Using a more specific, previously-reported alkyne-functionalized parthenolide probe (parthenolide-alkyne) (Shin et al, 2017), we observed multiple labeled proteins in 231MFP proteomes, of which some, but not all, targets were competed by parthenolide ( Fig. S1).…”
Section: Main Textmentioning
confidence: 85%
See 4 more Smart Citations
“…S1). Using a more specific, previously-reported alkyne-functionalized parthenolide probe (parthenolide-alkyne) (Shin et al, 2017), we observed multiple labeled proteins in 231MFP proteomes, of which some, but not all, targets were competed by parthenolide ( Fig. S1).…”
Section: Main Textmentioning
confidence: 85%
“…Parthenolide, a natural product found in the feverfew plant (Tanacetum parthenium), possesses myriad therapeutic activities, including anti-inflammatory and anti-cancer effects. Through covalent bond formation between its reactive a-methylene-g-butyrolactone moiety and various protein targets, multiple cellular signaling pathways are impacted (Ghantous et al, 2013;Kwok et al, 2001;Liu et al, 2018;Mathema et al, 2012;Shin et al, 2017). Moreover, this natural product belongs to the broader family of sesquiterpene lactones (estimated at > 5000 members), many members of which are also cytotoxic and have been hypothesized or shown to act through covalent mechanisms (Coricello et al, 2018;Quintana and Estévez, 2019).…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations